Share Economy - Identifikation von konstituierenden Merkmalen anhand einer vergleichenden Betrachtung von Geschäftsmodellen - Trykacz, Matthias

Reputation und Vertrauen auf Online-Märkten - Sonntag, Melissa

Rating Aggregation in Multi-Dimensional Rating Systems: How Do Reviewers Form Overall Ratings? - Gutt, Dominik; Kundisch, Dennis (INFORMS Annual Meeting)

Online Bewertungssysteme – Ein systematischer Überblick - Lange, Alexander

Erfolg durch Persönlichkeit? Der Einfluss der Markenpersönlichkeit auf den Zusammenhang von Reputation und Unternehmenserfolg - Fanasch, Patrizia

Die Veränderung des Mobilfunkmarktes durch die Discountanbieter - Walczok, Gregor Paul

How do reviews from professional critics interact with other signals of product quality? Evidence from the video game industry - Cox, Joe; Kaimann, Daniel (Journal of Consumer Behaviour)
Experience goods are characterised by information asymmetry and a lack of ex ante knowledge of product quality, such that reliable external signals of quality are likely to be highly valued. Two potentially credible sources of such information are reviews from professional critics and ‘word of mouth’ from other consumers. This paper makes a direct comparison between the relative influences and interactions of reviews from both of these sources on the sales performance of video game software. In order to empirically estimate and separate the effects of the two signals, we analyze a sample of 1480 video games and their sales figures between 2004 and 2010. We find evidence to suggest that even after taking steps to control for endogeneity, reviews from professional critics have a significantly positive influence on sales which outweighs that from consumer reviews. We also find evidence to suggest that reviews from professional critics also interact significantly with other signals of product quality. Consequently, we contend that professional critics adopt the role of an influencer, whereas word-of-mouth opinion acts more as a predictor of sales in the market for video games.

How do Different Sources of the Variance of Consumer Ratings Matter? - Herrmann, Philipp; Kundisch, Dennis; Zimmermann, Steffen; Nault, Barry (Proceedings of the 36th International Conference on Information Systems (ICIS), Fort Worth)
We examine the effect of the variance of consumer ratings on product pricing and sales using an analytical model, which considers goods that are characterized by experience attributes and informed search attributes (i.e., experience attributes that were transformed in search attributes by consumer ratings). For pure informed search goods, equilibrium price increases and demand decreases in variance. For pure experience goods, equilibrium price and demand decrease in variance. For hybrid goods with low total variance, equilibrium price and demand increase with an increasing relative share of variance caused by informed search attributes when the average rating and total variance of ratings are held constant. Hence, risk-averse consumers may prefer a more expensive good with a higher variance of ratings out of two similar goods with the same average rating. Moreover, our analytical model provides a theoretical foundation for the empirically observed j-shaped distribution of consumer ratings in electronic commerce.

Die Wirksamkeit von Zertifikaten als Qualitätssignal - Reimann, Alina

Trust Me, I am Certified - Wie die Zertifizierung von Produkten und Verkäufern das Vertrauen von Kunden im Onlinehandel beeinflussen - Ochlast, Kerstin

“…and they are really lying”: Clean Evidence on the Pervasiveness of Cheating in Professional Contexts from a Field Experiment. - Fahr, Rene; Mir Djawadi, Behnud (Journal of Economic Psychology)
We investigate the pervasiveness of lying in professional contexts such as insurance fraud, tax evasion and untrue job applications. We argue that lying in professional contexts share three characterizing features: (1) the gain from the dishonest behavior is uncertain, (2) the harm that lying may cause to the other party is only indirect and (3) lies are more indirect lies by action or written statements. Conducted as a field experiment with a heterogenous group of participants during a University ‘‘Open House Day’’, our ‘‘gumball-machineexperiment’’ provides field evidence on how preferences for lying are shaped in situations typically found in professional contexts which we consider to be particularly prone to lying behavior compared to other contexts. As a key innovation, our experimental design allows measuring exact levels of cheating behavior under anonymous conditions. We find clean evidence that cheating is prevalent across all sub groups and that more than 32% of the population cheats for their own gain. However, an analysis of the cheating rates with respect to highest educational degree and professional status reveals that students cheat more than non-students. This finding warrants a careful interpretation of generalizing laboratory findings with student subjects about the prevalence of cheating in the population.

Different Sources of the Variance of Online Consumer Ratings and their Impact on Price and Demand - Herrmann, Philipp; Kundisch, Dennis; Zimmermann, Steffen; Nault, Barry

Was tun um Kunden von der Qualität seiner Produkte zu überzeugen - Möglichkeiten der Zertifizierung und von Reputationssystemen auf Onlinemärkten - Lange, Maximilian

Conceptual Model and Economic Experiments to Explain Nonpersistence and Enable Mechanism Designs Fosterin Behavioral Change - Mir Djawadi, Behnud; Fahr, Rene; Turk, Florian (Value in Health)
BackgroundMedical nonpersistence is a worldwide problem of striking magnitude. Although many fields of studies including epidemiology, sociology, and psychology try to identify determinants for medical nonpersistence, comprehensive research to explain medical nonpersistence from an economics perspective is rather scarce.ObjectivesThe aim of the study was to develop a conceptual framework that augments standard economic choice theory with psychological concepts of behavioral economics to understand how patients’ preferences for discontinuing with therapy arise over the course of the medical treatment. The availability of such a framework allows the targeted design of mechanisms for intervention strategies.MethodsOur conceptual framework models the patient as an active economic agent who evaluates the benefits and costs for continuing with therapy. We argue that a combination of loss aversion and mental accounting operations explains why patients discontinue with therapy at a specific point in time. We designed a randomized laboratory economic experiment with a student subject pool to investigate the behavioral predictions.ResultsSubjects continue with therapy as long as experienced utility losses have to be compensated. As soon as previous losses are evened out, subjects perceive the marginal benefit of persistence lower than in the beginning of the treatment. Consequently, subjects start to discontinue with therapy.ConclusionsOur results highlight that concepts of behavioral economics capture the dynamic structure of medical nonpersistence better than does standard economic choice theory. We recommend that behavioral economics should be a mandatory part of the development of possible intervention strategies aimed at improving patients’ compliance and persistence behavior.

The Impact of Individual and Collective Reputation on Wine Prices: Empirical Evidence from the Mosel Valley - Frick, Bernd; Simmons, Robert (Journal of Business Economics)
Although of considerable practical importance, the separate impact of individual and collective reputation on firm performance (e.g. product prices) has not yet been convincingly demonstrated. We use a sample of some 70 different wineries offering more than 1,300 different Riesling wines from the Mosel valley to isolate the returns to individual reputation (measured by expert ratings in a highly respected wine guide) from the returns to collective reputation (measured by membership in two different professional associations where members are assumed to monitor each other very closely). We find that both effects are statistically significant and economically relevant with the latter being more important in quantitative terms than the former.